A shelter from the street families how Gawad Kalinga brings hope to the homeless - Buga-ay, Aileen P.
The purpose of this study is to determine the social, economic, spiritual, health and political effects of the Gawad kalinga community services to both Villages of Sooc, Arevalo and the Veterans Village, Duran Iloilo City. The vision of the Gawad Kalinga is to empower the dignity of the Street Families by building a better world and a better world and a better place as a self-reliant Christian Community. These vision is supported by the Iloilo City Government, Gawad kalinga, Iloilo City Task Force on Street Children, West Visayas College State University (WVCST), Philippine Ports authority (PPA) and NGO's such as Couples for Christ, Kids for Christ, Youth for Christ, Singles for Christ, Handmaids of the Lord and Servants of the Lord. PLDT, SMART, Iloilo Kinderhome, Inc. and other institutions.Using the purposive sampling method, thirty-three (33) respondents from the residents of Sooc, Arevalo and Veterans Village, Duran, Iloilo City were surveyed using the direct observation, interviews and questionnaires. Secondary data were gathered through examining some of the relevant literature. Based on the collated responses,the researcher present the following : On the availability of the services, it was determined that the livelihood, health and recreational programs are not in place yet. However, they regularly meet for their church assemblies. On safety, all of the residents in both villages feel safe living in the village. The lack of recreational facilities causes disagreements among thechildren in the village. There I an increase in the earnings of the majority of the residents, because of the recommendations for work coming from GK organizers. Scholarship grants are provided by the NGOs and other institutions to residents. These are skills training, vocational courses, nurses, elementary, high school and college education. The residents are aware ofwho plans and manages the projects for the villages. They exercise their right to choose their candidates during elections without being influenced by the GK management. To ensure sustainability of the community services, the residents should be provided education,appropriate follow-ups, and financial assistance needed as a start-up capital for livelihood. The GK management should plan for additional sports and recreational facilities that could promote unity, camaraderie and harmony among residents of both villages.